Increased Health Literacy Skills of High School Students with Media Likes - Purwanti, Kartika Yuni; Suryani, Ela; Rosyidi, M. Imron (International Journal of Community Service Learning, 2020)
This community service aims to make students able to do health literacy using media likes. The results of this training are that media likes can increase students 'understanding of health literacy by an average of 92.17%, namely students' understanding of health literacy increased by 35.87% (originally 64.13% to 100%), student empowerment in sorting information health increased by 36.74% (originally 46.75% to 83.49%), students' understanding of media likes increased by 56.24% (from 37.52 to 93.76%) and the use of media likes increased by 55.53% (from 35.91 to 91.44%). Media likes contain tips and tricks for doing health literacy, so they can sort out the right information. The results of the health literacy training activities can be said to be successful in the excellent category. Increased knowledge for training participants about health awareness, as well as sorting out health information circulating in the community.